OC63 Neonatal abstinence syndrome (NAS): how the timing of presentation influences a safe discharge policy. (June 2019) - Ibrahim, Mugahid; Pandey, Rajesh; Stark, Sydney; Ali, Ahmad; Gibson, Kelly; Bailit, Jennifer; Roy, Aparna; Kumar, Deepak; Philip, Roy K
Abstract : Background: Incidence of NAS from in-utero exposure to opioids has increased dramatically over the years in parallel with the general opioid uptake in societies. Management of NAS places social, emotional and financial burden on families and the health care systems. Age at which symptomatic NAS require pharmacological treatment is reported variably. Consequently, there is lack of consensus regarding the duration of observation to ensure safe discharge of the infant. Objective: To determine the optimal duration of postnatal hospital observation for at- risk infants following in-utero exposure to opioids. Design/Methods: A retrospective 5 year review of infants (≥36 weeks gestation) born between 2013–2017 to mothers with opioid dependency. Maternal and infant characteristics were abstracted from patient records and electronic database of the Mother and Child Dependency Program at Metro Health System, Cleveland, Ohio, USA. Age in hours of life (HOL) when pharmacological treatment was started for NAS as per guidelines was noted and confidence interval was defined. We compared infants who required pharmacological treatment within 96 to those who were treated beyond 96 hours using non-parametric tests. Results: Of the 355 infants with in-utero opiate exposure studied, 255(88.4%) required pharmacological treatment for NAS. Medications were initiated at a median age of 44.5 HOL (IQR 23–74.5 hours). 90±3% of infants were commenced on pharmacological treatment by 96 HOL; 93±3% by 120 HOL and 98±1% by 168 HOL (Figure-1). Infants who received treatment within 96 HOL (n=199) compared to those treated at >96 HOL (n=26) were more likely to have a urine toxicology positive for both mother and baby, have higher mean NAS score in first week of life, require a higher maximum dose of morphine and longer hospital stay. After adjusting for gestational age, breast milk exposure, methadone vs . buprenorphine maintenance programme, NICU vs. Special Care Unit admission; infants and mothers negative for drug screen (from those with history of in-utero exposure) were significant predictors for onset of NAS requiring pharmacological intervention at >96 HOL (OR 0.21; p value 0.011). Conclusions: The majority of infants who required pharmacological treatment for NAS during their postnatal observation period were diagnosed within the first 120 HOL. Those at- risk infants, born to mothers with a known history of exposure, who have a negative urine toxicology screen for both baby and mother, should be monitored beyond 5 days as they tend to have a later presentation.